Vision of East Central Europe in the thoughts of Polish intellectual elites of a 1989 turning point - Peciakowski, Tomasz (Political Preferences, 2018)
The thesis presented in this article advances that creation of the idea of East Central Europe, which was shaped by the social elite of Central-European nations since the 50s, played an essential role on the turn of 1989. The creation of such idea laid foundations of political talks and treaties on the recognition of borders. It reduced mutual claims and helped avoid conflict of borders and ethnic riots. Discussions between the elite of border nations reduced mutual prejudices and stereotypes, also in the context of relationships between the entire societies. In Poland, the deliberations on the idea of East Central Europe had later determined prerogatives of foreign policy conducted by the first non-communist governments and had become a manifestation of the fact that the country on the Vistula River had always been part of European civilization, separated by the Iron Curtain for several decades of the second half of 20th century. Key words: East Central Europe, intellectual elite, intellectuals, transformation, foreign policy